2017
DOI: 10.1177/1010428317695015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics—network analysis of proteins responsible for ursolic acid–induced cytotoxicity in colorectal cancer cells

Abstract: Ursolic acid is a key active compound present in many medicinal herbs that have been widely used in traditional Chinese medicine for the clinical treatment of various cancers. However, the precise mechanisms of its antitumor activity have been poorly understood. To identify the cellular targets of ursolic acid, two-dimensional gel electrophoresis combined with mass spectrometry was performed in this study, which identified 15 proteins with significantly altered levels in protein expression. This demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Natural compounds have been shown to have beneficial effects on a variety of cancer types [ 14 ]. UA, a pentacyclic triterpenoid compound found in herbs, spices, and the peels of fruits, has been shown to have anti-proliferative, pro-apoptotic, anti-inflammatory, anti-metastatic, and antiangiogenic properties against cancer cells [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Our study showed that UA significantly inhibited esophageal cancer cell growth in a dose-dependent manner and significantly attenuated colony formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural compounds have been shown to have beneficial effects on a variety of cancer types [ 14 ]. UA, a pentacyclic triterpenoid compound found in herbs, spices, and the peels of fruits, has been shown to have anti-proliferative, pro-apoptotic, anti-inflammatory, anti-metastatic, and antiangiogenic properties against cancer cells [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Our study showed that UA significantly inhibited esophageal cancer cell growth in a dose-dependent manner and significantly attenuated colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…Plants with significant UA content include apples (specifically the peel) and the leaves of oregano, rosemary, sage, eucalyptus, lavender, and coffee [ 16 ]. Several studies have shown that UA possesses anti-proliferative, pro-apoptotic, anti-inflammatory, anti-metastatic, and antiangiogenic properties against cancer cells [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. UA inhibits cell proliferation, arrests cell cycle progression, and reduces tumorigenesis through multiple signaling pathways [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Triterpenoid compounds such as ursolic acid, oleanolic acid, lupeol, avicins, oleanane, pristimer, and ursane demonstrate a variety of antitumor activities against breast cancer, skin cancer, ovarian cancer, non-small cell lung cancer, and prostate cancer (Kim et al ., 2016; Mendes et al ., 2016; Nakanishi et al ., 2016; Ren et al ., 2016; Wu et al ., 2016; Yin et al ., 2016). Ursolic acid (UA) is an attractive compound with potent anticancer activity in several types of cancers such as melanoma, leukemia, colorectal, lung, and breast cancers (Cai et al ., 2017). Ursolic acid displays various anticancer actions by reducing oncogene expression, modulating cell cycle, triggering apoptosis, suppressing metastasis, and regulating drug resistance (Zhang et al ., 2007; Manu and Kuttan, 2008; Lin et al ., 2013; Ou et al ., 2014; Xiang et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, activity of XBP1-s leads to promote CRC cell proliferation by inhibiting TAp73 transcriptional activity [ 32 ]; but Xbp1 reduces colorectal cancer cell proliferation and stemness by activating PERK signaling in CRC cell LS174T [ 33 ]. Studies reported that Heat Shock Protein 90 Beta Family Member 1 (HSP90B1), upregulated in many cancers [ 34 , 35 ], is a major contributor to evaluate the progression of carcinomas and may be a potential target for colorectal cancer therapy [ 36 ]. It is noteworthy that FA deficiency affected HSP90B1 only at the transcriptional level from our results of RT-qPCR and Western blotting.…”
Section: Discussionmentioning
confidence: 99%